An Overview on the Use of Response Surface Methodology to Model and Optimize Extraction Processes in the Food Industry. - AMIRPASHA TIRADO-KULIEVA, VICENTE; SÁNCHEZ-CHERO, MANUEL; VILLEGASYARLEQUÉ, MARIO; VILLEGAS AGUILAR, GRETELL FIORELA; CARRIÓN-BARCO, GILBERTO; YGNACIO SANTA CRUZ, ABRAHAM GUILLERMO; SÁNCHEZ-CHERO, JOSÉ (Current Research in Nutrition & Food Science, 2021)
Response surface methodology (RSM) is a widely used tool for modeling and optimization for food processes. The objective of this review is to evaluate recent findings on the use of RSM in the extraction of compounds from agrifood products. First, the steps for the application of RSM were briefly detailed. According to the analysis performed, RSM is suitable because it evaluates the effects of the independent variables and their interactions on the responses, which is ideal for the optimization of different techniques for the extraction of multiple bioactive compounds and therefore, in the various studies, has allowed to significantly increase the yield and even the biological activities of the extracts; however, RSM has limitations and considering the complexity and dynamics of foods, the challenge is much greater. In this sense, it was determined that simultaneous use with other techniques is necessary in order to optimally describe the process and obtain more accurate results.